THE INFLUENCE OF AMOUNT TOURISTS AND AMOUNT HOTEL ON RECEIVING HOTEL TAX - Sulistyowati; Hendrawati (International Journal of Social Science, 2021)
This study aims to analyze the effect of the amount of tourists, the amount of hotels on tax revenue. In an effort to support the existence of advanced, prosperous, independent, and just regional autonomy, they are faced with a challenge to prepare strategies in development planning. Proper planning by taking into account the potential of the region, especially in identifying the linkages between the hotel sector and other sectors. The analytical research technique used is t is multiple linear regression analysis. The results of this study indicate that the amount of tourists has an effect on hotel tax receipts while the amount of hotels does not affect hotel tax revenues. Based on the coefficient of determination the influence of the amount of tours and the amount of hotels has an effect of 63.2%. It is recommended to local and central governments to continue to increase the amount of tourist visits by increasing the development of the amount of tourist and entertainment places and having to hold events more often, both nationally and internationally.